Creek country : the Creek Indians and their world / Robbie Ethridge. - Ethridge, Robbie Franklyn, 1955- (University of North Carolina Press, 2003)
Reconstructing the human and natural environment of the Creek Indians in frontier Georgia, Mississippi, Alabama, and Tennessee, Ethridge presents a compelling portrait of a culture in economic, political, and ecological crisis; of its resiliency in the face of profound change; and of the forces that pushed it into decisive, destructive conflict.
Keywords: Creek Indians -- History.; Creek Indians -- Land tenure.; Creek Indians -- Government relations.; Creek Indians.; History.